Robot-Assisted Laparoscopic Radical Prostatectomy in a Short-Statured Man A Case Report - Iwanishi, Toshichika (Hinyokika kiyo. Acta urologica Japonica, 2022)
A 72-year-old man, who was extremely short-statured, underwent robot-assisted laparoscopic prostatectomy (RARP) for treatment of localized prostate cancer (cT1cNOMO). We report a case of congenital vertebral tip dysplasia with type II collagen dysplasia in a patient who underwent robot-assisted radical prostatectomy. Congenital vertebral tip dysplasia is characterized by short stature, and in this case, the height was 130 cm, which was equivalent to that of an 8-year-old child. The pelvic floor is narrow in short-statured individuals; therefore, the operative time tends to be longer than that required for routine surgery. However, using modifications in port positions and other adjustments, we performed RARP, and our perioperative results were similar to those obtained with routine RARPs